2016
DOI: 10.1371/journal.pone.0148064
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Decay of mRNA and Ribosomal RNA during Platelet Aging and Its Correlation with Translation Activity

Abstract: Previous investigations have indicated that RNAs are mostly present in the minor population of the youngest platelets, whereas translation in platelets could be biologically important. To attempt to solve this paradox, we studied changes in the RNA content of reticulated platelets, i.e., young cells brightly stained by thiazole orange (TObright), a fluorescent probe for RNAs. We provoked in mice strong thrombocytopenia followed by dramatic thrombocytosis characterized by a short period with a vast majority of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
92
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(101 citation statements)
references
References 57 publications
(77 reference statements)
8
92
1
Order By: Relevance
“…Similar variation was observed using published platelet RNA-Seq datasets from Rowley et al (supplemental Figure 3B). 23 Again, these data point to an underlying active process such as MK mRNA sorting 28 or platelet mRNA decay 11,13 shaping the platelet transcriptome and creating the broad variation in platelet enrichment we observed. A limitation of this analysis, however, is that the cultures of ex vivo-differentiated MKs used for RNA-Seq by Nürnberg et al contained 0% to 10% undifferentiated cells.…”
Section: Platelets Contain a Subset Of Mk Mrnasmentioning
confidence: 62%
See 3 more Smart Citations
“…Similar variation was observed using published platelet RNA-Seq datasets from Rowley et al (supplemental Figure 3B). 23 Again, these data point to an underlying active process such as MK mRNA sorting 28 or platelet mRNA decay 11,13 shaping the platelet transcriptome and creating the broad variation in platelet enrichment we observed. A limitation of this analysis, however, is that the cultures of ex vivo-differentiated MKs used for RNA-Seq by Nürnberg et al contained 0% to 10% undifferentiated cells.…”
Section: Platelets Contain a Subset Of Mk Mrnasmentioning
confidence: 62%
“…Based on these data, the typical mRNA decays with a half-life of 5.7 hours in PLPs (supplemental Figure 4A), consistent with recent measurements of bulk RNA turnover in primary platelets. 11 Histone mRNAs were somewhat shorter-lived (average half-life, 4.2 hours), whereas ribosomal protein mRNAs were slightly longer-lived than average (average half-life, 6.6 hours) (supplemental Figure 4B-C), and a few specific mRNAs seemed to be especially resistant to degradation, including MYD88 and RAP1A, which have special roles in platelets [75][76][77][78] ( Figure 4D). Taken together, these data suggest that RNA decay is likely a major driver that determines transcript abundance (and therefore to a significant extent translation) in platelets.…”
Section: Rna Decay Helps Shape the Nascent Plp Transcriptomementioning
confidence: 99%
See 2 more Smart Citations
“…By using RNA-Seq, they demonstrated that the half-life of mRNAs in cultured PLPs is 5.7 hours, a result that coincides with previous measurements of ex vivo mRNA decay in platelets. 5 Transgenic overexpression of PELO in PLPs significantly decreased the half-life of the majority of PLP mRNAs. Given that PELO expression is low in platelets, 7 these data suggest that megakaryocytes invest low levels of PELO into platelets as a mechanism for preserving mRNA levels in anucleate platelets that are incapable of transcribing new mRNA.…”
mentioning
confidence: 98%